Role of Brand Awareness And Brand Image On Customer Loyalty Through Customer Satisfaction As A Mediating Variable on 3 Second On The Shopee Marketplace - Saputra, Mochamad Adi; Anomsari, Ariati; Purwatiningsih, Aris Puji; Safitri, Maria (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the effect of brand awareness, brand awareness and brand image on customer loyalty, with customer satisfaction as a mediating variable on 3Second clothing products in the Shopee marketplace. Methodology: A quantitative approach is used using a questionnaire as the main data collection tool. The research sample was 105 consumers who had purchased 3Second hirt products on Shopee, which were dominated in Semarang City. Results: The path coefficient hypothesis test shows a direct effect between the independent variables on the dependent variable, that brand awareness and brand image have a positive and significant effect on customer satisfaction, customer satisfaction and brand awareness have a positive and significant effect on customer loyalty, while brand image has no effect on customer loyalty. Then the indirect effect is shown by the specific indirect effect test, namely that brand awareness and brand image have a positive and significant effect on customer loyalty through customer satisfaction as a mediating variable. The coefficient of determination (R²) on customer satisfaction of 0.514 indicates that customer satisfaction is influenced by these factors by 51.4%, while 48.6% is influenced by other variables not studied. Meanwhile, the R-Square value on customer loyalty of 0.511 indicates that customer loyalty is influenced by these factors by 51.1%, while 48.9% is influenced by other variables. Findings: The combined effect of brand awareness, brand image significantly affects customer satisfaction and customer loyalty. Originality: This study provides insight into consumer behavior in purchasing 3Second products on the Shopee marketplace. Novelty: This study highlights the importance of these factors in shaping customer satisfaction which is reinforced by customer loyalty in the context of 3Second clothing products on Shopee. Conclusion: Increasing brand awareness and brand image can increase customer satisfaction and customer loyalty. Type of Paper: Empirical research paper.